USE OF AUGMENTED REALITY TECHNOLOGIES IN SOFTWARE FOR INTERACTIVE VISUALIZATION OF THREE-DIMENSIONAL OBJECTS ON INDUSTRIAL SUBJECTS - Ulianovska, Y. V.; Rudyanova, T. M.; Oleshchuk, A. O.; Kostenko, V. V.; Bulhakova, O. F. (Systems and Technologies, 2021)
The digital economy is an important vector of the National Economic Strategy of Ukraine. The digital economy opens new opportunities and incentives for various areas of domestic business, including the development of industrial enterprises. Among the modern available digital technologies, the article considers one of the most promising technologies – augmented reality. Interest in augmented reality is shown by industrial enterprises that invest in its development, which contributes to its spread and improvement. This paper investigates the methods of application of AR in industry. The software application with the technology of interactive visualization of three-dimensional objects is implemented in the work. objects by means of augmented reality in real time and on a real scale with the function of storing and transmitting scenes with objects in space to mass mobile devices for implementation in industrial enterprises. Thanks to the existing scientific achievements in this field, analysis and synthesis of publicly available scientific works, the authors formed the main provisions of augmented reality and considered the main elements of this process in the chosen field. The experimental part of the work was performed using a set of development tools for ArCore tracking. A feature of the proposed system is the ability to create and manage a group of objects, presenting objects in real size and in real time for mass mobile devices. It was possible to change the parameters of augmented reality objects when visualized by entering a block of generalized parameters, which speeds up the interaction and includes the ability to change in real time and simplify the user interface. The mechanism and algorithm of manipulation of virtual three-dimensional objects in space with the use of input methods with the possibility of simultaneous movement and rotation, as well as the speed and stability of work and the technology of hiding objects are implemented. A promising area of the study is the application of developed technologies in various industries.